Adaptive digital watermarking system for authentication of intellectual properties - Olanweraju, Rashidah Funke; Abd Manaf, Azizah; Zeki, Akram M. (IIUM Press, 2011)
Digital information offers wonderful oppOltunities and improvements to human life, especially with the advent of internet. Such opportunities and improvements pose a great concern to all multimedia industries, especially intellectual properties. The fact is that the current digital distribution and storage technologies are great threat of counterfeiting and piracy where unlimited number of perfect copies can be produce illegally. The concerns over protecting intellectual property have triggered significant research in digital watermarking to solve the problem of piracy and counterfeiting. Digital watermarking is imperceptibly altering a host media to embed message or marks about the host can-ier itself, it hides message about an image, audio, text. video clip. or other work of media within that work itself, in such a way that is robust, secure and imperceptible to human observer, but can be detected algorithmically. This feature makes it useful in various applications such asauthentication, copy control, copy right protection etc. The principal advantage is that the content is inseparable from the watermark